Effect of La2O3 on the wear behavior of MoSi2 at high temperature - 张厚安 古思勇 谢能平 (Journal of rare earths, 2011)
Wear behaviors of MoSi2 doped with La2O3 against SiC under different loads at 1000 oC in air were investigated by using an XP-5 type high temperature friction and wear tester. The worn surfaces and phases of the samples were analyzed by scanning electron microscopy （SEM） and X-ray diffraction, respectively. Results showed that the addition of La2O3 could obviously improve wear resistance of MoSi2. Because of the formation of MoO3 phase on the worn surface, La2O3/MoSi2 composite mainly exhibited oxidation and abrasive wear, which was different from the wear form of MoSi2 such as adhesion, oxidation and abrasion.